TERRAIN ANALYSIS IN THE COURSE CURRICULA OF THE SOUTH AFRICAN ARMY ENGINEER CORPS - Lodi, K. P.; Smit, H. A. P.; Ayirebi, G. K. (Scientia Militaria - South African Journal of Military Studies, 2014)
The research reported here examined the engineer occupational course curricula presented by the South African Army School of Engineers. Methodology involved examination of all enabling learning objectives for the Corps Training Course (701 ENGR 006), the Troop Officers Course (701 ENGR 103), the Troop Commanders Course (701 ENGR 16) and the Squadron Commanders Course (701 ENGR 17). The research determined the number of learning objectives dedicated to terrain analysis and whether those learning objectives were linked to an assessment to determine competency levels for terrain analysis. The study used content analysis to determine the presence of terrain analysis content in the course curricula and to make recommendations. Data have been collected from analysis of the first four occupational course curricula presented to officers of the Engineer Corps as mentioned above, books, army field manuals and occasional papers. Recommendations are that the learning objectives dedicated to terrain analysis should be expanded and better focused and that assessment instruments capable of measuring competency in terrain analysis should be created and/or improved. An additional recommendation is that exercises are needed during the occupational courses that require officers to assimilate the effect of terrain on operations in order to improve officers’ terrain analysis competencies. This will serve as an important assessment instrument that will improve development of officers’ skills and earn them experience, not just grades.